Metal-polymer platinum nanocomposites for electrochemical conversion of hydrogen fuels in chemical power sources - M. V. Lebedeva; N. A. Yashtulov; N. E. Minina; B. A. Belyaev (Тонкие химические технологии)
For polymer Nafion films production containing Pt nanocomposites it was used the influence of gamma radiation 60Co. The platinum nanoparticles were synthesized by the method of radiation-chemical reduction of ions in reverse micelle solutions for subsequent Nafion films modification. It was demonstrated the effect of synthesis conditions, the degree of solubilization and nanoparticle sizes on the catalytic activity of Pt/Nafion nanocomposites. It was shown that the catalytic activity of metal-polymer nanocomposites increase with platinum nanoparticle size decreasing. Functional characteristics of nanocomposites were investigated by cyclic voltammetry and scanning electron microscopy methods. Created nano-catalysts showed high catalytic activity in the oxygen reduction and hydrogen oxidation reactions.